The Development of the DePaul Symptom Questionnaire: Original, Expanded, Brief, and Pediatric Versions - Jason, Leonard A.; Sunnquist, Madison (Frontiers in Pediatrics, 2018)
One of the key requirements of a reliable case definition is the use of standardized procedures for assessing symptoms. This article chronicles the development of the DePaul Symptom Questionnaire (DSQ) to assess symptoms of the major chronic fatigue syndrome (CFS) and myalgic encephalomyelitis (ME) case definitions. The original questionnaire has been modified and expanded over time to more fully capture symptoms from various adult case definitions, and a brief as well as pediatric version have also been developed. The DSQ has demonstrated strong psychometric properties in terms of test-retest reliability and sensitivity/specificity, as well as construct, predictive, and discriminant validity. The DSQ allows for a well-defined characterization of a patient’s illness and allows scientists and clinicians to improve diagnostic reliability when employing case definitions of ME and CFS.